STUDENTS’ PERCEPTION OF EXTENSIVE READING PRACTICE: A CASE STUDY AT UNIVERSITY STUDENTS - Soali, Muhammad (LPPM Universitas Harapan Bangsa, 2023)
Abstract This case study's goal is to examine the students’ perception with the application of extensive reading (ER) at university students. To learn more about The factors affecting the students’ success in ER class. Five EFL students of Harapan Bangsa University, Banyumas, Central Java, Indonesia, who are currently enrolled in their sixth semester as research participants selected on purpose based on three key factors, i.e. They are familiar with Extensive Reading and have taken ER courses. The information for this study was gathered using questionnaires, interviews, and diary entries from respondents. The information was then processed in accordance with Miles, Huberman, and Saldana's (2014) suggested stages of an interactive model of data analysis. There are two key conclusions from the analysis. First, the students contrasted their opinions on Extensive Reading Class. While one participant expressed joylessness and difficulty, four respondents reported enjoyment and motivation in the ER class. The students' different starting points in reading proficiency and the constrained freedom to choose what to read may all be pointed to as explanations for the finding. Second, according to the participants' perspectives, there are five elements that contribute to the success of an ER class: internal motivation, reading with initiative, a supportive reading environment, the availability of role model, and a variety of ER-based activities. Keywords: Extensive reading, Extensive reading class, Extensive reading Practice, Reading practice